Perlindungan Konsumen Terhadap Peredaran Produk Kesehatan Ilegal di Era Pandemik Covid-19 Di Kota Ambon - Theresia Louize Pesulima; Jenny Kristiana Matuankotta; Sarah Selfina Kuahaty (SASI, 2021)
This study swapped to know and analyze the protection of the law against consumen over the illicit circulation of health products in the covid-19 pandemic in the city of Ambon and the takes of the territory of the illegal health products in the covid -19 pandemic in the city of Ambon. The study was a sociolegal research. Which is the combination of research methods of doctrinal law research and empirical law research methods. The study was conducted in the municipal administration of Ambon, in the city of Ambon health services, in the industry and commerce of the province of Maluku and in the large hall of the Maluku drug and food centers. This type of data is primer data and seconder data through literature studies and interviews shown by the study shows that quality monitoring in done by both preventive and repressive governments in the pandemic covid-19 of Ambon, it is a legal protection for consumers against illegal health products that are unqualified and consumer helath standards and health that are circulated on the market according to prevailing legislation regulations.